Identifying Personal Characteristics of Social Media Entrepreneurs in Indonesia - Eliot Simangunsong (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2021)
Social media is currently not only used to communicate with friends but as a platform for business. This trend has been increasing since the Covid-19 pandemic, where more and more people are using it to buy and sell. However, there are doubts in running a business through social media, i.e., the absence of the right business strategy, understanding of business competition, and the personal characteristics of the people it needs. Therefore, this study aims to determine the ideal personal characteristics needed in running a social media-based business. Using qualitative research methods, data analysis from 20 interviews identifies twelve characters, six of which are critical to someone who has good potential to do business on social media and who can make the most of it. The suitability of an entrepreneur’s character and the demands of doing business on social media will lead to positive attitudes that are key to business success.